Noggin Combined With Human Dental Pulp Stem Cells to Promote Skeletal Muscle Regeneration - Zhang, Meng-Han; Yu, Li-Ming; Zhang, Wei-Hua; Deng, Jia-Jia; Sun, Bing-Jing; Chen, Mei-Hua; Huang, Wei; Li, Jiao; He, Hua; Han, Xin-Xin; Liu, Yue-Hua (Stem cells international, 2024)
A proper source of stem cells is key to muscle injury repair. Dental pulp stem cells (DPSCs) are an ideal source for the treatment of muscle injuries due to their high proliferative and differentiation capacities. However, the current myogenic induction efficiency of human DPSCs hinders their use in muscle regeneration due to the unknown induction mechanism. In this study, we treated human DPSCs with Noggin, a secreted antagonist of bone morphogenetic protein (BMP), and discovered that Noggin can effectively promote myotube formation. We also found that Noggin can accelerate the skeletal myogenic differentiation (MyoD) of DPSCs and promote the generation of Pax7 + satellite‐like cells. Noggin increased the expression of myogenic markers and the transcriptional and translational abundance of satellite cell (SC) markers in DPSCs. Moreover, BMP4 inhibited Pax7 expression and activated p‐Smad1/5/9, while Noggin eliminated BMP4‐induced p‐Smad1/5/9 in DPSCs. This finding suggests that Noggin antagonizes BMP by downregulating p‐Smad and facilitates the MyoD of DPSCs. Then, we implanted Noggin‐pretreated DPSCs combined with Matrigel into the mouse tibialis anterior muscle with volumetric muscle loss (VML) and observed a 73% reduction in the size of the defect and a 69% decrease in scar tissue. Noggin‐treated DPSCs can benefit the Pax7 + SC pool and promote muscle regeneration. This work reveals that Noggin can enhance the production of satellite‐like cells from the MyoD of DPSCs by regulating BMP/Smad signaling, and these satellite‐like cell bioconstructs might possess a relatively fast capacity for muscle regeneration.